2018
DOI: 10.1177/1555412018791697
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond Churn: Barriers and Constraints to Playing a Social Network Game

Abstract: Social network games (SNGs) are genre of casual games that require being logged into a social networking site (e.g., Facebook) to access the gameworld. To date, investigations of these games are typically focused on the rate of attrition or "churn," reinforcing the idea that SNG players exist to make the developer money rather than participating in a game they derive pleasure from. Seeking to recenter the player in research about SNGs, this article reports on a survey of former players (N ¼ 147) who were queri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
0
21
1
Order By: Relevance
“…That women made up more of the solo players who ultimately left gaming in our sample suggests the need for future research to better understand if the lack of family members to play with (Cluster 4) has an impact on their decision to ultimately quit. While our previous research has found that women are more likely to quit playing in order to care for a family member [2], to date we have not encountered women who describe a lack of family to play with ultimately causing them to leave gaming. Future research is required to unpack the possible implications for this finding.…”
Section: Social Playmentioning
confidence: 76%
See 1 more Smart Citation
“…That women made up more of the solo players who ultimately left gaming in our sample suggests the need for future research to better understand if the lack of family members to play with (Cluster 4) has an impact on their decision to ultimately quit. While our previous research has found that women are more likely to quit playing in order to care for a family member [2], to date we have not encountered women who describe a lack of family to play with ultimately causing them to leave gaming. Future research is required to unpack the possible implications for this finding.…”
Section: Social Playmentioning
confidence: 76%
“…Because our previous findings suggest that women are more likely to have constraints on their leisure time than men [2,4], we deliberately over sampled women in order to collect as many as possible open ended survey responses from former and non-players. Our overall numbers were corrected back to being a representative US sample using the following methods.…”
Section: Resultsmentioning
confidence: 99%
“…In this article, I continue my previous research that disrupts biological deterministic arguments surrounding who plays what games and for what reasons (Bergstrom, 2019a(Bergstrom, , 2019c. Throughout my work, I have argued that gendered assumptions about who plays digital games, what games they play, and for what reasons they play are complicated when feminist games scholarship is put into conversation with leisure scholarship.…”
Section: Barriers To Digital Gameplaymentioning
confidence: 78%
“…Investigations into why users leave other online communities, such as the communities that invariably form around online multiplayer games, found that players often leave for reasons beyond a personal lack of interest and instead there are internal or external forces that push a user towards disengagement (Bergstrom, 2019;Jiang, 2018;Poor & Skoric, 2014). Our goal here is to better understand why users disengage from Reddit.…”
Section: Disengaging From Online Communitiesmentioning
confidence: 99%